Pro: Live high + train low does improve sea level performance beyond that achieved with the equivalent living and training at sea level - Wilber, R. L. (High Altitude Medicine & Biology, 2014)
In conclusion, evidence from several well-designed investigations over the past 15 years suggest that LH+ TL altitude training is an effective method for enhancing sea level performance in endurance athletes, including athletes at the elite/Olympic level, provided a sufficient altitude/hypoxic ``dose`` is attained. At present, it appears that one of the major mechanisms affecting sea level endurance performance following LH+ TL is an increase in total hemoglobin mass and oxygen-carrying capacity, although there is emerging evidence that other non-hematological mechanisms may be involved. L H+ TL continues to evolve for the purpose of identifying optimal training protocols for use by athletes from a variety of endurance sports. siehe auch http://online.liebertpub.com/doi/full/10.1089/ham.2013.1080